The river experiment centre Andong:A unique near prototype outdoor flume facility (2020)
Recognizing the importance of improving our knowledge about the complex interactions between hydrologic regime, geomorphic evolution of river channels and the associated interactions with vegetation and biologic responses combined with the difficulties of scaling many riverine processes down to the laboratory scale, the Korean Institute of Civil Engineering and Building Technology (KICT, see textbox) has developed one of the largest river experimentation facilities in the world, the River Experiment Center (REC), in Andong. The REC has a total area of 200,000 m 2 and was designed for full scale tests with three prototype channels (600 m long and 11 m wide) and a large capacity pump facility with a controllable flow rate up to 10 m 3 /s and a flow velocity up to 5 m/s. Additionally, a 100 m long and 30 m wide hydraulic model test basin and a retention pond are also part of the premises equipped for various kinds and scales of river experiments.